2014
DOI: 10.1177/1559827614538750
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of Exercise for People Living With HIV

Abstract: With life expectancy increasing and the symptomatology of HIV being altered since the advent of antiretroviral therapy (ART), we now have begun to see metabolic changes with negative implications among people living with HIV/AIDS (PLWHA). Some of these changes include increased blood lipids, central fat accumulation, lipodystrophy, and decreased aerobic capacity. All of which are known risk factors for cardiovascular disease, cancer, and all-cause mortality. A common practice among healthy and other clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 54 publications
5
59
1
1
Order By: Relevance
“…The evidence grade rating of this effect is high and therefore, may have signi cant clinical importance. The ndings of this study agree with evidence from other studies [1,15,43,44], which reported on the effectiveness of physical exercises in ameliorating depression in PLWHA. Previous studies provided evidence where both aerobic and resistance exercise have independent and combined positive effects on various indicators of mental health in people living with HIV [41].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The evidence grade rating of this effect is high and therefore, may have signi cant clinical importance. The ndings of this study agree with evidence from other studies [1,15,43,44], which reported on the effectiveness of physical exercises in ameliorating depression in PLWHA. Previous studies provided evidence where both aerobic and resistance exercise have independent and combined positive effects on various indicators of mental health in people living with HIV [41].…”
Section: Discussionsupporting
confidence: 92%
“…Evidence regarding the effectiveness of exercise training on depression favours exercise when compared to control and suggests that Combinational exercise ( important implications for practice, especially in sub-Saharan African where despite the existing evidence of the bene cial value of physical activity in ameliorating symptoms of mental health, yet physical activity is neglected as a routine rehabilitation modality in the mental healthcare systems [61]. Importantly, mood disorders, which is common in HIV conditions due to the infection and side effects of the medication (HAART) in patients, have also been linked to poor adherence to medications and consequently, poor health outcomes [1][2][3][4][5][6]. If physical activity/exercises ameliorate symptoms of mood disorders (depression), it may also improve adherence to medication and likewise other related health outcomes.…”
Section: Conclusion Implications For Practicementioning
confidence: 99%
See 2 more Smart Citations
“…El paciente debe realizar ejercicio aeróbico de moderada intensidad y entrenamiento de resistencia de manera progresiva 5 veces por semana, durante al menos 30 minutos/día. Esto tendrá efectos positivos en la acumulación de grasa corporal, dislipidemias y capacidad aeróbica pero sin cambios en la carga viral y el recuento de CD4+ [15].…”
Section: Terapia Recomendadaunclassified